1983
DOI: 10.1128/jvi.48.1.197-205.1983
|View full text |Cite
|
Sign up to set email alerts
|

Chemical cleavage of polyomavirus major structural protein VP1: identification of cleavage products and evidence that the receptor moiety resides in the carboxy-terminal region

Abstract: As a first step toward identifying the various functional regions of the polyomavirus major capsid protein VP1, we used recently developed methods for the chemical cleavage of proteins and the available polyomavirus sequence data to devise a scheme to produce large, identifiable peptides and generate a cleavage map of VP1. Formic acid (75%) was found to cleave VP1 at only two sites, producing three peptides of apparent molecular weights of 29,000, 16,000, and 2,000. The order of peptides in intact VP1 was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…3, lane 2). In vitro surface labeling of polyomavirus virions along with immunological studies have enabled us to suggest that the 29-kDa peptide is cryptic within the virion structure and that the 18-and 16-kDa fragments of VP1, which are exposed on the virion surface, are involved in virus attachment to host cells (1,7,22,25). Calcium binding has previously been shown to be important in maintaining protein conformation (18,28).…”
Section: T-pro La-lys-asn-glu-asn-thr-arg-tyr 240 Phe-gly-asn-tyr-thrmentioning
confidence: 99%
See 1 more Smart Citation
“…3, lane 2). In vitro surface labeling of polyomavirus virions along with immunological studies have enabled us to suggest that the 29-kDa peptide is cryptic within the virion structure and that the 18-and 16-kDa fragments of VP1, which are exposed on the virion surface, are involved in virus attachment to host cells (1,7,22,25). Calcium binding has previously been shown to be important in maintaining protein conformation (18,28).…”
Section: T-pro La-lys-asn-glu-asn-thr-arg-tyr 240 Phe-gly-asn-tyr-thrmentioning
confidence: 99%
“…Localization of the 45Ca-binding domain on the VP1 protein was achieved by first isolating this protein from an SDS-polyacrylamide gel for cleavage into discrete peptides by using formic acid (1). The resulting peptide cleavage products were then separated by SDS-PAGE and electroblotted for use in probing with 45CaC12.…”
mentioning
confidence: 99%
“…This interest has directed us to investigate in detail the attachment species D, E, and F of the major structural protein VP1, since we have previously shown that these species are responsible for host cell receptor interaction as well as the hemagglutinating ability of the virus (3). Studies have been conducted which indicate that the polyomavirus hemagglutinin and receptor functions reside in, or at least have determinants contained in, the carboxy-terminal 153 amino acids of the VP1 sequence (1). Previous reports have suggested that polyomavirus binding to the host cell surface is a two-step process (3,4,18,21): a nonspecific step involving VP1 species D and F and a specific step involving species E. Polyomavirus agglutination of GPE is believed to be nonspecific, involving species D and F, since both complete virions and empty capsids have this ability yet capsids lack VP1 species E. MKC-py, which exhibited a 10-fold greater ability to agglutinate GPE than that of MEC-py (Table 1), also demonstrated greater nonspecific binding ability to host cells than MEC-py did ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This charge heterogeneity is due at least in part to phosphorylation (1-3, 15, 29, 30), since three of the identified species (D, E, and F) are phosphorylated (2,3). Our laboratory is particularly interested in these three phosphorylated species since we have shown previously that these species correlate with the hemagglutination ability of the virus as well as specific cellular attachment (1,(3)(4)(5).…”
mentioning
confidence: 96%
“…While enormous progress has been made in this field by using de novo designed synthetic peptides (2), the idea of using protein fragments obtained by chemical or enzymatic methods (3) has been only rarely pursued (4). Chemical methods, although equally selective in cleaving proteins on selected residues, are always carried out under harsh conditions that invariably lead to protein unfolding (5). On the other hand, enzymatic proteolysis of folded proteins performed under mild conditions, occurs preferentially on exposed and less structured sites (6,7), and thus can help to isolate shorter polypeptides with partially preserved secondary and tertiary structures.…”
mentioning
confidence: 99%